Ring opening of photogenerated azetidinols as a strategy for the synthesis of aminodioxolanes - Maag, Henning; Lemcke, Daniel J.; Wahl, Johannes M. (Beilstein Journal of Organic Chemistry, 2024)
α-Aminoacetophenones are identified as promising building blocks for the synthesis of highly substituted dioxolanes. The presented strategy is founded on the build and release of molecular strain and achieves a formal transposition of a methyl group. During light irradiation, 3-phenylazetidinols are forged as reaction intermediates, which readily undergo ring opening upon the addition of electron-deficient ketones or boronic acids. Key to the successful development of this two-step process is the identification of a benzhydryl-protecting group, which orchestrates the photochemical Norrish–Yang cyclization and facilitates the subsequent ring opening.
Keywords: azetidine; Norrish–Yang cyclization; ring-opening reaction; ring strain